2023
DOI: 10.1136/rmdopen-2023-003160
|View full text |Cite
|
Sign up to set email alerts
|

Drug retention of biologics and Janus kinase inhibitors in patients with rheumatoid arthritis: the ANSWER cohort study

Kosuke Ebina,
Yuki Etani,
Yuichi Maeda
et al.

Abstract: ObjectivesThis multicentre retrospective study in Japan aimed to assess the retention of biological disease-modifying antirheumatic drugs and Janus kinase inhibitors (JAKi), and to clarify the factors affecting their retention in a real-world cohort of patients with rheumatoid arthritis.MethodsThe study included 6666 treatment courses (bDMARD-naïve or JAKi-naïve cases, 55.4%; tumour necrosis factor inhibitors (TNFi) = 3577; anti-interleukin-6 receptor antibodies (aIL-6R) = 1497; cytotoxic T lymphocyte-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…On the contrary, a multicenter retrospective study on b/tsDMARDs revealed that the concomitant use of oral glucocorticoids at baseline was associated with the discontinuation of b/tsDMARDs due to their ineffectiveness, 24 with which our results are consistent.…”
Section: With Glucocorticoids N = 160 P-valuesupporting
confidence: 68%
See 1 more Smart Citation
“…On the contrary, a multicenter retrospective study on b/tsDMARDs revealed that the concomitant use of oral glucocorticoids at baseline was associated with the discontinuation of b/tsDMARDs due to their ineffectiveness, 24 with which our results are consistent.…”
Section: With Glucocorticoids N = 160 P-valuesupporting
confidence: 68%
“…Examination sites included bilateral wrist and first to fifth metacarpophalangeal and proximal interphalangeal joints every 3 months after the introduction of b/tsDMARDs. Systematic multiplanar grayscale (GS) and power Doppler (PD) joint examinations were performed using a multifrequency linear transducer (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and one of the following scanners: Toshiba AplioXG, Aplio300 or Aplioi800, GE Logic series 7 or 8 or HITACHI HI VISION Avius, and Noblus or HI VISION Preirus. All scanners were the latest machines available at the time of the study with joint mode.…”
Section: Ultrasound Assessmentmentioning
confidence: 99%
“…While investigating the predisposing factors of a retention rate, the ranking order of DMARD administration is consistently retained in multivariate analysis as statistically significant 13 14 17 with a better drug retention rate when the drug was initiated as the first or second biologic line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is why, in RWD studies, the percentage of patients still on treatment over time, known as the drug retention rate, has been proposed as a surrogate measure of drug efficiency. [11][12][13] Studies conducted by pharmaceutical companies after drug approval are referred to as postmarketing surveillance studies. 13 These studies are often based on RWD and are typically conducted shortly after the drug becomes available in a specific country (launch time), particularly when mandated by health authorities.…”
Section: What Does This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation